2022
DOI: 10.1177/21925682221117130
|View full text |Cite
|
Sign up to set email alerts
|

Revision Surgery After Spinal Fusion in Adolescent Idiopathic Scoliosis

Abstract: Study design Retrospective Aanalysis of a Large Cohort of Cases. Objectives To explore the rate and cause of revision surgery after spinal fusion in adolescent idiopathic scoliosis(AIS). Methods The patients diagnosed with AIS who underwent spinal fusion surgery in a single center from 2002 to 2018 were retrospectively analyzed. All the patients were followed up at least 2 years. The causes of revision surgery were analyzed and the incidence of revision surgery was counted. Results A total of 1816 AIS patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Regarding postoperative infection, deep infection occurred in 31.4% (11 of 35 cases), while superficial infection occurred in 25.7% (9 of 35 cases) [11]. The most common longer term postoperative complications are pseudarthrosis, curve progression, and proximal junctional kyphosis [15]. Among these, postoperative infection, pseudarthrosis, and curve progression are the most frequent causes of revision surgery, accounting for 34%, 26%, and 17% of reoperations, respectively [16].…”
Section: Complications and Reasons For Revisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding postoperative infection, deep infection occurred in 31.4% (11 of 35 cases), while superficial infection occurred in 25.7% (9 of 35 cases) [11]. The most common longer term postoperative complications are pseudarthrosis, curve progression, and proximal junctional kyphosis [15]. Among these, postoperative infection, pseudarthrosis, and curve progression are the most frequent causes of revision surgery, accounting for 34%, 26%, and 17% of reoperations, respectively [16].…”
Section: Complications and Reasons For Revisionmentioning
confidence: 99%
“…Revisions due to decompensation, adding on, and junctional kyphosis occur mainly 2-5 years after the primary operation, while revisions due to wound and instrumentationrelated complications, such as infection and malposition, mainly occur less than 2 years after operation [15]. A study by El Rachkidi et al [27] reported that patients were never re-operated on before 3 months postoperative to allow for spontaneous correction.…”
Section: Complications and Reasons For Revisionmentioning
confidence: 99%